Landlord William Scully - Socolofsky, Homer E., 1922-2005 (Book collections on Project MUSE., 1979)
Landlord William Scully presents a full picture of the investment and landmanagement activities of one of the most important figures in American agricultural history. An Irishman who first came to the United States in 1850, Scully eventually built up holdings amounting to almost a quarter million acres of the richest prairie and farm lands in Illinois, Nebraska, Kansas, and Missouri. The vast land empire, which was worked by some fifteen hundred tenant farmers, earned for Scully the reputation of being America's greatest landlord--this despite the fact that he remained an alien until the last decade of his life.